Evaluation of Spinosad as a Packaging Treatment Against Three Species of Coleoptera - Freijat, Julie; Scheff, Deanna S. (My University, 2018)
Spinosad is a natural insecticide derived from the fermentation of the soil dwelling bacteria, Saccharopolysporaspinosa (Hertlein et al., 2011; Toews et al., 2003). Spinosad has been shown to be a highly effective as a surface treatment on concrete, steel, and tile against several stored product insects (Toews et al., 20013). Packaged food products are highly susceptible to infestation by stored product insects by penetration or invasion of packaging material. Infestations of packaged products result in product losses, economic losses, and loss of consumer confidence. Incorporating traditional contact or low-risk insecticides into packaging materials are new approach to pests management and has been gaining increasing interest among food manufacturing companies (Scheff et al., 2017). Incorporating Spinosad into packaging material is a novel technology that could prevent infestations of packaged food products.
Keywords: Fall 2018